The Extent of Participation and Empowerment of Rural Women in Lac Cultivation in Koderma District of Jharkhand, India - Chanchila Kumari; Jyoti Sinha; Debrup Ghosh; A K Rai (Archives of Current Research International, 2024)
Lac cultivation in Koderma District, Jharkhand, offers a unique pathway for empowering rural women, serving as a significant source of income and socio-economic upliftment. This review examines the depth of women’s participation in various stages of lac production, from inoculation to processing, and how their involvement translates into empowerment. Despite facing challenges like gender discrimination, limited access to resources, and market constraints, women in Koderma have demonstrated resilience and adaptability. Lac cultivation has provided them with financial independence and enhanced social recognition and decision-making power within their households and communities. Initiatives by the government and NGOs have played a critical role in facilitating this shift, offering training, market access, and financial support to enable women to break socio-cultural barriers. However, for sustained empowerment, addressing the existing gaps in technology access, market linkage, and equitable resource distribution is essential. This article aims to explore lac cultivation’s role in empowering rural women in Koderma District, Jharkhand, by examining their participation in the production process and its impact on their socio-economic upliftment (Pal G., 2011). It aims to highlight women’s challenges, the contributions of government and NGO initiatives, and the need for improved policies, technology, and market access to ensure sustained empowerment and equitable participation in the lac industry.